Direct observation of t2g orbital ordering in magnetite - Schlappa, Justina; Haverkort, Maurits W. (Arxiv, 2007)
Using soft-x-ray diffraction at the site-specific resonances in the Fe L23 edge, we find clear evidence for orbital and charge ordering in magnetite below the Verwey transition. The spectra show directly that the (001/2) diffraction peak (in cubic notation) is caused by t2g orbital ordering at octahedral Fe2+ sites and the (001) by a spatial modulation of the t2g occupation.